Comparative Analysis and Scrutiny of Key Authentication Techniques in Fully Homomorphic Schemes - Pooja Dhiman, Dr.Santosh Kumar Henge (International Journal of Advanced Science and Technology, 2020)
This research paper is focused on various past proposed approaches, methodologies, lagging issues, advantages of various Fully Homomorphic Encryption schemes. FHE supports unlimited number of operations on ciphertext. These operations can be sorting, searching, multiplicative, additive or mixed. The four FHE schemes namely, Non-interactive Exponential Homomorphic Encryption Algorithm, Brakerski-Gentry-Vaikuntanathan, Enhanced Homomorphic cryptosystem, Algebra Homomorphic encryption scheme based on updated ElGamal are analysed. It is observed that BGV and AHEE support static and dynamic data both. AHEE is indistinguishable under CPA (Chosen plaintext attack) only; it is not CCA (chosen ciphertext attack) secure. Implementation of BGV scheme is available easily still it is a little difficult to implement in real life applications due to overhead of managing storage. Researchers can refer this paper to study these schemes in detail. Based on the requirement, particular scheme or a combination of schemes can be chosen.